Entrepreneurship addiction : exploring patterns of engagement with venturing activities - Spivack, April J.; McKelvie, Alexander (Entrepreneurship footprints series, 2022)
"April J. Spivack and Alexander McKelvie present the development of the concept of entrepreneurship addiction, contributing to wider discussions of the 'dark side' of entrepreneurship. Focusing attention on mental health issues and neurodiversity among entrepreneurs, it offers insights into conflicting findings regarding entrepreneurial well-being. The book incorporates contemporary multifaceted lenses that consider cognitive, emotional, biological and physiological dimensions of experience, highlighting the complex interplay between entrepreneurs and their ventures. It distinguishes entrepreneurship addiction from other behavioural addictions to develop a robust and distinct empirical measure of psychological and physiological health of entrepreneurs. Describing recent contributions to this rapidly developing field of study, Spivack and McKelvie supply key research tools and map out a research agenda for further investigation. Offering operational methodologies for the study of entrepreneurial addiction, this book is crucial reading for scholars of entrepreneurship interested in the psychological and behavioural impacts of entrepreneurial endeavours. It will also benefit career-driven entrepreneurs, their partners, family members, and others looking for personal insights into entrepreneurial behaviour, as well as mental health workers and practitioners"--